Pengaruh Jumat Berkah Terhadap Peningkatan Kesadaran Sosial dan Keagaaman Pada Mayarakat Sekitas Yayasan Al-Ikhlas Sidoarjo - Rahmadhani, Adilya; Musthofa, Chabib (PROGRESIF: Jurnal Dakwah, Sosial, dan Komunikasi, 2024)
This study is aimed at studying the influence of the blessing of Friday tradition, organized by the Al-Hilas Foundation in Great Kebon Agung, Sukodono, Sidoarjo, and more and more social and religious consciousness about the surrounding community. This tradition includes the active participation of citizens in the form of donations of food and basic needs distributed among destitute people every Friday in the morning. This study uses qualitative methods with unstructured interviews and non-participant observation as data collection methods. The research results show that the Friday Blessing Program plays an important role in increasing social empathy, strengthening relationships among residents, and enhancing people's religious awareness. Apart from providing material assistance, this tradition also contributes to strengthening values ​​of solidarity and deepening awareness of Islamic teachings, especially in terms of sharing and compassion for others. The program is considered effective in creating a more caring and religious social environment, as well as encouraging people to actively participate in faith-based social activities.